Early recognition of the diagnostic criteria of a patient with sepsis and implementation of the one-hour package per nurses: a cross-sectional study (Brazilian Journal of Health Research, 2023)
Introduction:Sepsis is defined when an infectious agent (viruses, bacteria or fungi) affects the immune system, causing an unregulated response of the body, compromising the proper functioning of the organs, causing their failure, being fatal, most of the time. In order to obtain a positive prognosis in a patient with sepsis, it is necessary to identify the clinical picture early, where the nursing team is assumed to be easier, since care is direct and continuous. Objective: To evaluates the knowledge of nurses about the early recognition of the diagnostic criteria of a patient with sepsis and implementation of the one-hour package. Methods: A cross-sectional study was conducted with 60 nurses working in the municipal hospitals of Quixadá and Quixeramobim, in October 2019. Results: the sociodemographic characterization showed that the majority of nurses were females (41; 89%); aged between 31 and 59 years (25; 54%); single (29; 63%); and with five or more years of form (29; 63%). When analyzing the knowledge of nurses, it was noticed that most of them know the concept of sepsis (41; 89%); what is a sepsis protocol (38; 83%); and all (46; 100%) claim do not have a protocol implemented in their workplace. Conclusion: there is a satisfactory knowledge by nurses about sepsis and its main characteristics, with an important percentage of bureaucratic difficulties pointed out that impact on the existence, use and implementation of the protocol in their services.